2017
DOI: 10.1080/20477724.2017.1396411
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hypertension and its selected risk factors among adult tribal population in Central India

Abstract: A community based cross-sectional study was carried out to assess the prevalence of hypertension and associated risk factors like salt intake, 24-h urinary sodium excretion and body mass index (BMI) among tribal population of Mandla District, Central India. A total of 3090 individuals, from 1258 house hold drawn from 33 sampled villages and 12 urban wards were studied for blood pressure measurements and clinical examination, while 414 urine samples were collected for estimation of 24-h sodium excretion. Bivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 15 publications
(17 reference statements)
7
16
1
Order By: Relevance
“…Some recent studies have noted a high prevalence of hypertension in tribal populations in northeast India. 30 , 31 A systematic review of primary hypertension among 53 tribal populations indicated a pooled prevalence of 16.1%, which was very close to our adjusted estimate of 15.7%. 32 The best evidence on the secular increases in risk factor prevalence in India, however, has been limited to urban areas of southern India, which are more likely to be among the higher SES groups.…”
Section: Discussionsupporting
confidence: 81%
“…Some recent studies have noted a high prevalence of hypertension in tribal populations in northeast India. 30 , 31 A systematic review of primary hypertension among 53 tribal populations indicated a pooled prevalence of 16.1%, which was very close to our adjusted estimate of 15.7%. 32 The best evidence on the secular increases in risk factor prevalence in India, however, has been limited to urban areas of southern India, which are more likely to be among the higher SES groups.…”
Section: Discussionsupporting
confidence: 81%
“…47 Chakma et.al have observed a higher prevalence of hypertension among those who consume salt >10 g/per day, which indicates a positive association of salt intake with hypertension; as the mean salt intake increases blood pressure levels also increase. 26 Many other studies have also provided similar evidence that greater salt consumption is associated with higher levels of blood pressure. 48,49 According to a study by Hazarika et al 50,51 the added salt in the tea and local alcohol consumption are significant risk factors of HTN among tea garden workers of Assam.…”
Section: National Nutrition Monitoring Bureau (Nnmb) Tribalmentioning
confidence: 76%
“…About 90% of them live in rural areas and only 10% live in urban areas. In general, Scheduled Tribes (STs) inhabit two distinct geographical areas; Central India and North-Eastern India (Chakma et al 2017). Manipur is a tiny state situated in the easternmost part of North Eastern region of India.…”
mentioning
confidence: 99%